Literature Review: Foot Exercise Prevents the Risk of Neuropathy on Diabetes Mellitus Patient: Foot Exercise Prevents the Risk of Neuropathy on Type 2 Diabetes Mellitus Patient - Ryan Hidayat; Chita Widia (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Aims : Diabetes mellitus is a disease in which the body cannot automatically control glucose in its blood, a complication that often occurs in the lower limbs called diabetic feet. This study aims to determine the risk of neuropathy in type 2 diabetes mellitus sufferers who perform diabetic foot exercises. Design :The research design is the Literature Review type of Narrative Review. Methods :The literature search in this literature review uses two databases with high and medium quality criteria, namely Scopus, and Google Scholar, using keywords technique in English which arranged into one search sentence are "Foot Diabetic Exercise "OR" Foot Exercise "AND" Prevention "OR" Prevent "OR" Avoid "AND" Neuropathy" AND" Risk of Neuropathy "OR "low situational self esteem". Results :The number of samples was 7 articles whose research title was about the effect of diabetic foot exercise on the risk of neuropathy in type 2 diabetes mellitus sufferers in the last ten years of publication. Conclusions :Diabetic foot exercises to reduce the risk of neuropathy in type 2 diabetes mellitus sufferers.